2014
DOI: 10.1371/journal.pone.0094054
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Evaluation of Peripheral Nerve Regeneration in the Acute Healing Phase Using Tissue Clearing and Optical Microscopy in a Rodent Model

Abstract: Peripheral nerve injury (PNI), a common injury in both the civilian and military arenas, is usually associated with high healthcare costs and with patients enduring slow recovery times, diminished quality of life, and potential long-term disability. Patients with PNI typically undergo complex interventions but the factors that govern optimal response are not fully characterized. A fundamental understanding of the cellular and tissue-level events in the immediate postoperative period is essential for improving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 42 publications
0
26
0
2
Order By: Relevance
“…1, Supplementary Fig. 1)111920212223242526. Collection of pump light, after the lasers' SRS interaction with the sample in focus, was achieved by the use of a high numerical aperture condenser and band-pass filter before detection with a photodiode (Methods section and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1, Supplementary Fig. 1)111920212223242526. Collection of pump light, after the lasers' SRS interaction with the sample in focus, was achieved by the use of a high numerical aperture condenser and band-pass filter before detection with a photodiode (Methods section and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore next tested the utility of SRS imaging in the context of a mouse model of axonal injury by sciatic nerve crush22232642. The sciatic nerve of one hind limb was crushed in WT and SOD1 G93A animals then imaged distally of the injury at both 1 week and 3 weeks after initial injury (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An important application is the visualization of the myelin sheath in the central nervous system (2628, 96, 97) and the peripheral nervous system (98, 99), which provides an effective way to study spinal cord injury and myelin disease ex vivo (Figure 2 c , left ) and in vivo (Figure 2 c , middle and right ). In Figure 2 c , the myelin sheath, myelinated axons, and the node of Ranvier are highlighted (from left to right) with good contrast in CARS images.…”
Section: Applications Using Crs Microscopymentioning
confidence: 99%
“…The quantitative measurement of lipid storage has also been applied to identify 9 out of 272 genes whose inactivation increased fat content by more than 25% (98). Studies of myelin disease and spinal cord injury used CRS microscopy at the tissue level to visualize the myelin sheath in the central (99103) and peripheral (104, 105) nervous systems. For medical imaging, Freudiger et al (89) and Ji et al (106) showed that, by the linear combination of SRS images at peaks of 2,850 and 2,940 cm −1 for CH 2 and CH 3 vibration modes, a stain-free histopathological image comparable to a hematoxylin and eosin (H&E) stained image can be achieved (Figure 3 a ).…”
Section: Single-frequency Coherent Raman Scattering Microscopymentioning
confidence: 99%